Determination of Chloramphenicol (CAP) Residues by LC-MS/MS in Shrimp Available in Commercial Markets of Lahore - Hadyait, Muhammad Arfan; Ali, Asif; Bhatti, Ehsan Mahmood; Qayyum, Aroosa; Ullah, Muhammad Zafar (International Journal of Nanotechnology and Allied Sciences, 2018)
Eighty seven samples of shrimps (Penaeus indicus) were randomly collected from four major markets of Lahore. The samples were transported to Fish Quality Control Labs Lahore. The shrimps were tested for the presence of chloramphenicol (CAP) on LC-MS/MS using negative ion mode and electron spray source. The CAP was not detected in any of the collected samples. It is concluded that shrimps sold in different markets of Lahore are safe for human consumption.